A new search direction of DFP-CG method for solving unconstrained optimization problems - Wan Farah Hanan Wan Osman; Mohd Asrul Hery Ibrahim; Mustafa Mamat (2018)
The conjugate gradient (CG) and Davidon, Fletcher and Powell (DFP) method are both well known solvers for solving unconstrained optimization problems. In this paper, we proposed a new hybrid DFP-CG method and compared with the ordinary DFP method in terms of number of iteration and CPU times. Numerical results show that the new algorithm is more efficient compared to the ordinary DFP method and proven to posses both sufficient descent and global convergence properties.